Calibration of a panoramic 3D reconstruction system. Issue 6 (21st March 2019) - Córdova‐Esparza, Diana Margarita; González‐Barbosa, José‐Joel; Terven, Juan R.; Hurtado‐Ramos, Juan B.; Almaraz‐Cabral, César‐Cruz
Abstract : Owing to their large field of view, a catadioptric imaging system is widely used in several research areas, including robot navigation, surveillance, and three‐dimensional (3D) reconstruction. The modelling and calibration of these systems allow the accurate measurement of objects. This paper presents a calibration method for a panoramic 3D reconstruction system based on pattern projection composed of two modules. The first module, which contains a charged coupled device camera and a parabolic mirror allows the acquisition of catadioptric images. The second module is a catadioptric projection system made of a light projector and a parabolic mirror that generates a projected pattern over the target for reconstruction purposes. Both the modules are calibrated independently. The method achieves a reprojection error of 0.6 pixels in the camera module and 1.2 pixels in the catadioptric projection system. To evaluate the performance of the proposed method, the results show 3D reconstructions of multiple objects with tolerances around 1.3 mm.